Eigenvalues bounds for symmetric interval matrices. (2015) - Singh, Sukhjit; Gupta, D.K.
The aim of this paper is to approximate the eigenvalues bounds of real symmetric interval matrices as sharp as possible. Using the concepts of interval analysis, this is done by solving the standard interval eigenvalue problem by applying the interval extension of the single step eigen perturbation method. The deviation amplitude of the interval matrix is considered as a perturbation around the nominal value of the interval matrix. The mathematical formulation of the method is described. Two numerical examples are worked out and the results obtained are compared with the results of existing methods. It is observed that our method is reliable, efficient and gives better results for all examples considered.